2023
DOI: 10.4314/tjpr.v22i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Leonurine inhibits breast cancer cell growth and angiogenesis via PI3K/AKT/mTOR pathway

Abstract: Purpose: To elucidate the effect of leonurine on the proliferation, invasion, migration, and angiogenetic potential of breast cancer cells. Methods: Human breast cancer cell line (MDA-MB-231) and normal breast cell line, (SK-BR-3) were cultured. Both cell lines were treated with 200, 400, or 800 μM leonurine and cultured for 0 (control), 24, 48, or 72 h. Cell counting kit-8 (CCK8) and colony formation assays were performed to measure cell viability and proliferation. Invasion and migration were evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Leonurine alkaloid, the primary active biological alkaloid contained within Motherwort, has been acknowledged for its extensive array of biological functions and its exceptional antitumor properties Leorita et al, 2020;Liu et al, 2021;Liang et al, 2022). The cornerstone of Leo's antitumor actions primarily hinge upon its anti-inflammatory and antioxidant activities Tian et al, 2023). Additionally, Leonurine exhibits capacity to impede tumor cell cycles, induce apoptosis in tumor cells, and stimulate the immune system.…”
Section: Abstract Leonurine Anti-tumor Mechanisms Signal Transduction...mentioning
confidence: 99%
“…Leonurine alkaloid, the primary active biological alkaloid contained within Motherwort, has been acknowledged for its extensive array of biological functions and its exceptional antitumor properties Leorita et al, 2020;Liu et al, 2021;Liang et al, 2022). The cornerstone of Leo's antitumor actions primarily hinge upon its anti-inflammatory and antioxidant activities Tian et al, 2023). Additionally, Leonurine exhibits capacity to impede tumor cell cycles, induce apoptosis in tumor cells, and stimulate the immune system.…”
Section: Abstract Leonurine Anti-tumor Mechanisms Signal Transduction...mentioning
confidence: 99%
“…The results of the CCK8 assay, colony formation assay, and colony formation assay showed that LEO significantly inhibited MDA-MB-231 or SK-BR-3 cell proliferation at 400–800 μM concentrations. Moreover, in this dose range, LEO dose-dependently inhibited cell migration, invasion, and angiogenesis ( Tian et al, 2023 ). High-risk human papillomavirus persistent infection and genetic factors are the principal causes of cervical cancer ( Revathidevi et al, 2021 ).…”
Section: Pharmacodynamics Of Leomentioning
confidence: 99%
“…Leonurine alkaloid, the primary active biological alkaloid contained within Motherwort, has been acknowledged for its extensive array of biological functions and its exceptional antitumor properties ( Zhu et al, 2018 ; Leorita et al, 2020 ; Liu et al, 2021 ; Liang et al, 2022 ). The cornerstone of Leo’s antitumor actions primarily hinge upon its anti-inflammatory and antioxidant activities ( Lin et al, 2020 ; Chen et al, 2023 ; Tian et al, 2023 ). Additionally, Leonurine exhibits capacity to impede tumor cell cycles, induce apoptosis in tumor cells, and stimulate the immune system.…”
Section: Introductionmentioning
confidence: 99%